2019
DOI: 10.1111/odi.13114
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin‐10 gene polymorphisms and severe chronic periodontitis

Abstract: Objective Periodontitis is an inflammatory disease that is a result of the interaction between pathogenic bacteria and host immune response. Genetic alterations in interleukin‐10 (IL‐10) gene may be associated with the increased risk of periodontitis. We investigated the association between genotype and haplotype frequencies of IL‐10 gene polymorphisms and susceptibility to periodontitis in an Iranian population. Methods In this case–control study, a total of 64 patients with periodontitis and 128 healthy subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The study revealed a protective role of the G allele against CPO. Almost similar results were obtained by Emampanahi et al [21] in the same population. Several other Asian studies [22][23][24][25] also indicated such a role of the G allele of IL-10-1082 G/A polymorphism against CPO.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study revealed a protective role of the G allele against CPO. Almost similar results were obtained by Emampanahi et al [21] in the same population. Several other Asian studies [22][23][24][25] also indicated such a role of the G allele of IL-10-1082 G/A polymorphism against CPO.…”
Section: Discussionsupporting
confidence: 89%
“…Several other Asian studies [22][23][24][25] also indicated such a role of the G allele of IL-10-1082 G/A polymorphism against CPO. Emampanahi et al [21] revealed that the AGC haplotype (-592/-1082/-819) haplotype was higher in healthy subjects, while AAC (-592/-1082/-819) was markedly higher among patients with CPO. The protective mechanism of the G-allele and its associated genotypes is related to the position of this polymorphism in the promoter region of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…They participate in systemic inflammation and play vital roles in innate and adaptive immunity. Previous studies had indicated that IL gene SNPs associate with the development of both bacteria-and virus-related inflammatory disorders, such as sepsis [9,10], periodontitis [11,12], hepatitis B [13], and C [14] virus infections. However, current studies were still limited regarding the potential associations between IL gene SNPs and the risks of developing PTOM, especially in Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…A few IL-10 promoter polymorphic sites have been characterized with determination of three polymorphisms from transcription initiation site at positions -819 (rs1800871), -592 (rs1800872) and -1082 (rs1800896) (-1082) (46). These IL-10 promoter polymorphisms have been the most widely investigated in various diseases: asthma, cardiovascular diseases, diabetic nephropathy, systemic lupus erythematosus, rheumatoid arthritis, chronic periodontitis, Alzheimer's disease (47)(48)(49)(50)(51)(52)(53). Furthermore, these polymorphisms are strongly associated with various serum levels of IL-10 in vivo (54).…”
Section: Snp Selectionmentioning
confidence: 99%